Impacts of Community Pharmacists on Self-medication Management among Rural Dwellers, Kwara State Central, Nigeria - Bello, Shakirat I; Bello, Ibrahim K (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The role of pharmacist has not only advanced from medication dispensing but also to direct patient care and pharmaceutical interventions aiming at enhancing the populace wellbeing. The objective of this research was to assess the impact of rural community pharmacist interventions on self-medications and disease prevalence among rural settings in the Kwara State Central, Nigeria. A descriptive, cross-sectional study was conducted in eight rural communities with a pre-piloted questionnaire. Data obtained from respondents were computed with Statistical Package for Social Sciences (SPSS) Version 16 using descriptive analysis procedures, and relationships between variables were tested using the chi square. Respondents between the age of 40 and 50 years dominated with 42.3% and majority (88.1%) of the rural residents were illiterates. Farming was the major occupation of the respondents and survived on less than ten thousand naira Nigeria money (63) per month. Among the combinations of drugs abused by the respondents, the regimen containing combination of prednisolone, diclofenac and paracetamol had the highest users. The least used combination was ibuprofen, diclofenac plus prednisolone. These combinations were taken twice daily by the majority participants. The most common reasons given for self-medications were osteoarthritis (31.1%), poverty (17.4%), general body pain (14.3%), inadequate of health facilities (4.6%), ignorance (4.3%) among others. The intervention offered by the pharmacists had reduced the mean systolic blood pressure significantly (P < 0.05) from 161 mmHg to 129 mmHg and diastolic blood pressure from 104 mmHg at baseline to 86 mmHg. Postintervention evaluation revealed the impact of the pharmacists, as the respondents with dyspepsia at baseline significantly (P < 0.05) reduced from 220 to 53 participants. Dhaka Univ. J. Pharm. Sci. 12(1): 1-9, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16294